Post-mortem shrinkage of homograft aortic valves. Issue 3 (May 1972) - Dexter, F.; Donnelly, R. J.; Deverall, P. B.; Watson, D. A.
Abstract : Experience has shown that some frame-mounted homograft aortic valves, although competent immediately after mounting, are incompetent when subsequently presented for surgical use. Retraction and shrinkage of the cusps appears to be the cause of this change. Clinical and experimental studies have shown that shrinkage of homograft aortic valves occurs over an approximately five-day period after death of the donor and it is recommended that this period should elapse before mounting homograft aortic valves on to support frames.